Association of reduced glyoxalase 1 activity and painful peripheral diabetic neuropathy in type 1 and 2 diabetes mellitus patients - Skapare, Elina; Konrade, Ilze; Liepinsh, Edgars; Strele, Ieva; Makrecka, Marina; Bierhaus, Angelika; Lejnieks, Aivars; Pirags, Valdis; Dambrova, Maija (Elsevier, 2013)
Aims: The present study was undertaken to investigate the relationship between glyoxalase 1 (Glo1) enzyme activity and painful diabetic neuropathy (DN) in patients with diabetes mellitus. Methods: Glo1 activity and biochemical markers were determined in blood samples from 108 patients with type 1 diabetes, 109 patients with type 2 diabetes, and 132 individuals without diabetes as a control. Painful and painless peripheral DN was assessed and multivariate regression analysis was used to determine independent association of Glo1 activity with occurrence of painful DN. Results: In patients with type 1 and type 2 diabetes mellitus and painful DN compared to patients with painless DN, Glo1 activity was significantly reduced by 12 and 14%, respectively. The increase in Glo1 activity was significantly associated with reduced occurrence of painful DN after adjusting for confounders by multivariate analysis. Conclusions: Our results demonstrate for the first time that Glo1 activity is lower in patients with both types of diabetes mellitus who were diagnosed with painful DN. These data support the hypothesis that Glo1 activity modulates the phenotype of DN and warrant further investigation into the role of Glo1 in DN. © 2013 Elsevier Inc. All rights reserved.
Keywords: Research Subject Categories::MEDICINE; Glyoxalase 1; Diabetes mellitus; Painful diabetic neuropathy; Type 1 diabetes; Type 2 diabetes